The Effect of Particle Dispersion due to Mixing Speed on Spent Coffee Ground Composites - Sumarji, Sumarji; Ridha, Fabrobi; Dwilaksana, Dedi; Syuhri, Ahmad; Raihaan, Raihaan (Universitas Pendidikan Indonesia, 2019)
Composites using bio-materials with unique properties, such as spent coffee ground were developed for composite fillers. This study was conducted to produce samples under various mixing speed conditions. This study also determined effect of mixing speeds on particle homogeneity as well as composite dispersion in the final product. The composite dispersion was determined by an index based on a standard deviation of free-path spacing of filler particles using a digital microscope. Results showed that when using high-speed mixing, particle tends to agglomerate with particle clumps. We also obtained that faster mixing speed results more homogeneous mixture compared to slower speed. In short, slower speed can reach similar result in homogeneity levels, but it would require longer time for the mixing process.